Study of mitotic activity and chromosomal behaviour of the root meristem of Allium cepa L. treated with cartap hydrochloride - Parajuli, Tilak P; Sakya, Shyam R (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.24-26